2019
DOI: 10.1007/s00203-019-01749-2
|View full text |Cite
|
Sign up to set email alerts
|

Microaerobic conditions caused the overwhelming dominance of Acinetobacter spp. and the marginalization of Rhodococcus spp. in diesel fuel/crude oil mixture-amended enrichment cultures

Abstract: The aim of the present study was to reveal how different microbial communities evolve in diesel fuel/crude oil-contaminated environments under aerobic and microaerobic conditions. To investigate this question, aerobic and microaerobic bacterial enrichments amended with a diesel fuel/crude oil mixture were established and analysed. The representative aerobic enrichment community was dominated by Gammaproteobacteria (64.5%) with high an abundance of Betaproteobacteriales (36.5%), followed by Alphaproteobacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 95 publications
(96 reference statements)
0
22
0
Order By: Relevance
“…Although these strains did not harbour subfamily I.2.C-type C23O gene, this lineage of the genus Pseudomonas seems to be adapted to microaerobic environments. Earlier we have observed the dominance of these bacteria in microaerobic, crude oil/gasoline mixture–degrading enrichment cultures (Benedek et al 2018 ; Révész et al 2020 ), and it was reported that P. extremaustralis preferably degrades alkanes under microaerobic conditions (Tribelli et al 2018 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although these strains did not harbour subfamily I.2.C-type C23O gene, this lineage of the genus Pseudomonas seems to be adapted to microaerobic environments. Earlier we have observed the dominance of these bacteria in microaerobic, crude oil/gasoline mixture–degrading enrichment cultures (Benedek et al 2018 ; Révész et al 2020 ), and it was reported that P. extremaustralis preferably degrades alkanes under microaerobic conditions (Tribelli et al 2018 ).…”
Section: Resultsmentioning
confidence: 90%
“…The sampled biofilm continuously developed on the stainless steel surface of a submersible pump, which was part of a pump-and-treat system operating at the contaminated site. In previous enrichment studies, this continuously emerging biofilm was successfully used to study the biodegradation of petroleum hydrocarbons under microaerobic conditions (Benedek et al 2018 ; Révész et al 2020 ). Members of the class Gammaproteobacteria overwhelmingly dominated the bacterial community of the newly sampled biofilm material (47% of 16S rDNA sequence reads) (Online Resource 1 , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, under full aerobic conditions, no hydrocarbon degradation occurred (Tribelli et al 2018). Moreover, Révész et al (2019) also found the dominance of P. extremaustralis/P. veronii lineage-related bacteria in diesel fuel/crude oil mixture-amended enrichment cultures.…”
Section: Discussionmentioning
confidence: 85%
“…While both genera are commonly found in hydrocarbon-contaminated environments, hydrocarbon substrates have only been shown to enrich and select for different Psychrobacter phylotypes [68][69][70]. Janthinobacteria, on the other hand, are believed to tolerate petroleum hydrocarbon toxicity rather than using oil components as carbon sources [71], although, indirect measurements (i.e., community structure analysis of contaminated soils based on 16S rRNA genes) hint at their hydrocarbon degrading capabilities [72,73]. Likewise, the petroleum hydrocarbon degradation activity of S. quinivorans, which was most closely related to Serratia sp.…”
Section: Discussionmentioning
confidence: 99%